157k views
3 votes
Given that the first term is: T1 = 2, and the recursive definition is: t n + 1 = 3 ( t n ), what would be the 2nd term

Group of answer choices

3

9

27

81

2 Answers

0 votes

Answer: 9

Step-by-step explanation: i got a 100

User Vishal Singh
by
4.9k points
7 votes

Answer:

The second term of the sequence is T(2) = 6.

Explanation:

Here, the first term is given as

T(1) = 2

The general Formula for nth term is given as:

T(n + 1) = 3(T(n))

Now, here the second term

for, n = 1

T(1+1) = 3 (T(1))

or, T(2) = 3 T(1)

⇒ T(2) = 3 x 2 = 6

Hence, the second term of the sequence is T(2) = 6.

User Mykola Pavlov
by
5.3k points